An unexpectedly low Stratus optical coherence tomography false-positive rate in the non-nasal quadrants of Asian eyes: indirect evidence of differing retinal nerve fibre layer thickness profiles according to ethnicity. Issue 6 (3rd June 2008) - Kim, T W; Kim, T-W; Park, K H; Kim, D M
Abstract : Aims: To determine the frequency distribution of false-positive Stratus optical coherence tomography (OCT) results of healthy eyes in terms of peripapillary location. Methods: One eye of each of 137 healthy Korean subjects was included. The false-positive rates (FPRs) relating to retinal nerve fibre layer (RNFL) thickness parameters were determined. Results: Of the 12 clock-hour positions, the 2 and 4 o'clock positions showed the highest FPRs of 5.1% and 4.4%, respectively, and 7, 8 and 11 o'clock had the lowest FPRs of 0% at <5% level. At <1% level, 2 and 6 o'clock had an FPR of 0.7%, while the FPR was 0% for all other clock-hours. The FPRs for quadrant thicknesses at <5% level were: 0.7% for temporal; 0% for superior; 5.1% for nasal; and 2.2% for inferior. At <1% level, the inferior showed the highest FPR of 0.7%, and the other three quadrants 0%. According to line graph analysis, the 80–120 test point sections had FPRs of 4.4–6.6%, while the 0–40 and 210–256 sections were 0–0.7% at <5% level. At <1% level, the 40–60, 90–110 and 200–210 sections had 0.7%, 190–200 section 1.5%, and all other sections 0%. Conclusion: The FPR for the non-nasal region was much lower than expected at <5% level. Given that the current OCT normative database is based on a largely non-Asian population, these findings suggest that RNFL thickness profiles may differ according to ethnicity.